2020
DOI: 10.37358/mp.20.1.5312
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation, Modeling and Optimization of Circularity, Cylindricity and Surface Roughness in Drilling of PMMA Using ANN and ANOVA

Abstract: In this paper, experimental investigation, modeling and optimization of the drilling of PMMA are performed using the Taguchi Design of Experiments (DOE), analysis of variance (ANOVA) and artificial neural networks (ANN) methods. Drilling experiments were conducted on PMMA to assess the impact of process parameters (drill diameter, spindle speed, and feed rate) on the hole-quality characteristics (surface roughness, circularity error, and cylindricity error). ANOVA was performed to identify the drilling paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 15 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In order to develop a relationship between input and output parameters, they utilized a feed-forward backpropagation neural network consisting of two hidden layers. The results showed that the developed models have a maximum absolute mean relative error of 7% [ 36 ]. Karthik et al incorporated the CCDOE to study the effect of spindle speed, feed rate, and depth of cut on surface roughness AISI 316 under face milling operation.…”
Section: Introductionmentioning
confidence: 99%
“…In order to develop a relationship between input and output parameters, they utilized a feed-forward backpropagation neural network consisting of two hidden layers. The results showed that the developed models have a maximum absolute mean relative error of 7% [ 36 ]. Karthik et al incorporated the CCDOE to study the effect of spindle speed, feed rate, and depth of cut on surface roughness AISI 316 under face milling operation.…”
Section: Introductionmentioning
confidence: 99%
“…Around 410 research articles were reported on experimental work on different spindle speed and feed rate on google scholar and 153 out of it were published in science directly. (Susac and Stan 2020) in this study an experimental investigation on the aluminum 6061 to optimize of the circularity,cylindricity and the surface roughness of the drilling done with different spindle speed and feed rate.and observe at which speed the surface roughness and cylindricity tolerance are optimize with the nearest values. (Zaidi 2016) this research is about knowing the physical properties of the aluminum 6061chips using the hot extrusion process.how the metal chips are removed during the drilling process.based on the spindle speed.…”
Section: Introductionmentioning
confidence: 95%
“…A three-layer ANN model with a sigmoid transfer function with back-propagation algorithm between the input and the hidden layer and a linear transfer function between the hidden and the output layer was used in this study [5,20,22,23,42,43]. The architecture of the ANN model used to predict the flow length is shown in Figure 11 The input layer has four neurons corresponding to the design variables, such as melt temperature, spiral thickness, injection pressure, and mold temperature, whereas the output layer have two nodes, i.e., flow length and spiral weight.…”
Section: Architecture and Training Of The Ann Modelmentioning
confidence: 99%